ВЛИЯНИЕ ДУХОВНО-ЭСТЕТИЧЕСКОГО ВОСПИТАНИЯ НА РАЗВИТИЕ ЛИЧНОСТИ В ПРОЦЕССЕ ОБРАЗОВАНИЯ - Абдурахманова, А.Т. (SCIENCE and SOCIETY, 2020)
The state pays great attention to young people, has determined as a priority of state policy, defined the tasks of forming the spiritual and aesthetic education of the future generation. In teaching , it is an important factor in educating students in the spiritual, moral and aesthetic directions.
Keywords: education; upbringing; training; priorities in politics; spirituality; morality; aesthetics